Synthesis and Character ation of Novel (Co (II), Ni{11>, .cuM, Zn en>, and Cd(ll)) Binuclear Complexes of N, N- his [(2, 4, 6-trihydroxy metbyl)] Benzidine - Nlunan, A.. T.; Alkazweeni, M.T.; Yousi, E. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The Synthesis C!}f    a;  rw;v Schiff  base ligan-d .N  ' N  - bis(2> 4,6-trjpr;diOXY meth)l) benz1dine l 6L] aAd its c.omplexes w.ithÂ·  Co 1ll 1 , Ni('ll);cu< IÂ·>     Zn(ll) .and Cd(TJJ are  reported . The  ltgand   was  prepared  by  thereaction           of          4,4-aniino-biphenyl            benzidine     with     2,4;6Â· tnliydro yace ophenon mQnohydmte ander  reflux in m tbaool as solvent and a few drops of glacial  acetic   qid  . Then theÂ·complexes were synthes by-Â· adding the cqnÂ·esp-onding metal  salts  to  the  solution  of rhe ligah.d  in meth nol under. reflux \vith 2:1 metal to liga.nd  ralio.  Orr 'the  basis of, molar conductance, I.R., UV-Vischloride  content and atomic  absorption the complex-es may he formt:rlated asÂ·[M2 {HtL) CI2.2J--bO]  [M=CmNi,CuÂ·.Zn  and Cd] . The data of these j measur:ements suggest a tetrahedra,! g(:!qrnetry Ito Cd.'11\  Gu0!J Zn(ll) ,and cd